Apical status and prevalence of endodontic treated teeth among Saudi adults in Eastern province: A prospective radiographic evaluation - Khalaf A. Al-Awasi; Ghada A. Altaroti; Mustafa A. Aldajani; Abeer Assaf Alshammari; Marwah Ahmed Almunasif; Abdulrahman Abdullah M. AlQarni; Mohammed Ameer Aldokhi; Tarek Ezzeldin; Intisar Ahmad Siddiqui (Saudi Dental Journal, 2022)
Introduction: The main cause for developing periapical lesions (PA) is the root canal infection. The mentioned causes may play a role in not controlling it but are not a “true” cause. Objective: To determine apical status and prevalence of endodontic treated tooth using radiograph assessment in relation to quality of root canal treatment and clinical factors among Saudi adults in the Eastern province. Patients and methods: This prospective case series study included 2161 patients who received root canal treatment (RCT) at Dammam Specialized Dental Center, Dammam Medical Complex, Ministry of Health, Saudi Arabia, between October 21, 2019 and April 22, 2020, after getting ethical approval from the Institutional Research Board (IRB). Saudi natives of either gender, age ≥ 18, with at least one fixed bridge or single dental crown evaluated on a clear, high-quality radiography image were recruited for the study. To determine the periapical state of root canal-filled teeth, the 'periapical index' (PAI) was used. All pertinent patient information was analyzed in SPSS verion-20 (IBM product, Chicago). Results: Out of 2161 cases, a PA lesion was present in 756 (35.0%). The prevalence of periapical lesions in endodontically treated teeth was 31.2%. PA lesion was associated with molar involvement (50.8% vs. 36.6%, p = 0.001), poor RCT quality (85.2% vs. 51.0%, p = 0.001), and smoking (13.6% vs. 10.5%, p = 0.028). According to logistic regression model, female gender, molar tooth, and poor RCT quality were more likely to expose PA lesion 1.5 times, 1.8 times, and 5 times, respectively. Conclusion: It is concluded that approximately 1/3rd of endodontically treated teeth are susceptible to the occurrence of periapical lesions in radiographic assessment, which are significantly associated with females, molars, and poor RCT quality, indicating a challenge for endodontists to improve their root canal assessment accuracy.